Perceived poverty and health, and their roles in the poverty-health vicious cycle: a qualitative study of major stakeholders in the healthcare setting in Hong Kong - Gary Ka-Ki Chung; Dong Dong; Samuel Yeung-Shan Wong; Hung Wong; Roger Yat-Nork Chung (BMC, 2020)
Abstract Background Poverty and ill-health are closely inter-related. Existing studies on the poverty-health vicious cycle focus mainly on less developed countries, where the identified mechanisms linking between poverty and ill-health may not fit the situations in developed Asian regions. This study aims to qualitatively explore the perceived mechanisms and drivers of the poverty-health vicious cycle among major stakeholders in the healthcare setting in Hong Kong. Methods Data were collected via focus group interviews with social workers (n = 8), chronically ill patients (n = 8), older adults (n = 6), primary care doctors (n = 7) and informal caregivers (n = 10). The transcribed data were then closely read to capture key themes using thematic analyses informed by social constructivism. Results In this highly developed Asian setting with income inequality among the greatest in the world, the poverty-health vicious cycle operates. Material and social constraints, as a result of unequal power and opportunities, appear to play a pivotal role in creating uneven distribution of social determinants of health. The subsequent healthcare access also varies across the social ladder under the dual-track healthcare system in Hong Kong. As health deteriorates, financial hardship is often resulted in the absence of sufficient and coordinated healthcare, welfare and labour policy interventions. In addition to the mechanisms, policy drivers of the cycle were also discussed based on the respondents' perceived understanding of the nature of poverty and its operationalization in public policies, as well as of the digressive conceptions of disease among different stakeholders. Conclusions The poverty-health vicious cycle has remained a great challenge in Hong Kong despite its economic prosperity. To break the cycle, potential policy directions include the adoption of proportionate universalism, social integration and the strengthening of medical-social collaboration.